Status and perspectives of hydrogenated amorphous silicon detectors for MIP detection and beam flux measurements - Menichelli, M.; Servoli, L.; Wyrsch, N. (Frontiers in Physics, 2022)
Hydrogenated amorphous silicon (a-Si:H) particle detectors have been considered as alternatives to crystalline silicon detectors (c-Si) in high radiation environments, due to their excellent radiation hardness. However, although their capability for particle flux measurement in beam monitoring applications is quite satisfactory, their minimum ionizing particle (MIP) detection has always been problematic because of the poor signal-to-noise ratio caused by a low charge collection efficiency and relatively high (compared to crystalline silicon) leakage current. In this article, after a review of the status of technological research for a-Si:H detectors, a perspective view on MIP detection and beam flux measurements with these detectors will be given.